A STUDY ON VISHAGHNA PROPERTY OF SHANKHPUSHPI (CONVOLVULUS PLURICAULIS CHOIS) W.S.R. TO SUB ACUTE TOXICITY IN ALBINO WISTAR RATS (AYUSHDHARA, 2019)
Shankhpushpi (Convolvulus pluricaulis chois) is an indigenous and very significant herb which is considered as a gift of nature in Ayurveda. In Ayurvedic literature, Shankhpushpi is considered as Medhya rasayana means it enhances the knowledge, memory and retaining power of a person. Shankhpushpi which is well described and abundantly available is taken for the Vishaghna property also. Although, the Medhya property of Shankhpushpi is well marketed and used by different pharmaceutical companies but, the Vishaghna property of this miraculous drug should be researched and established as it may fulfil the long awaited gap of Ayurvedic antitoxic substance(Agad).In this study 24 albino wistar rats were divided in four groups such as group G1, G2, G3 & G4 with 6 rats in each group. Group G2, G3 & G4 had received PCM in dose 1000mg/kg body weight for 7 days to induce hepato-nephro toxicity while group G1 was normal control group which was kept on normal feeding. After inducing hepato-nephro toxicity the sample drug Shankhpushpi in Group G2 in the form of Churna and in group G3 in the form of aqueous extract (Kwatha) was administered while in group G4 only normal saline was administered for 28 days. On the basis of study it can be concluded that toxicity induced by 1000mg/kg body weight PCM did not cause any neurological manifestations. After 28 days administration of drug Shankhpushpi Churna as well as Kwatha in group G2 & group G3, body weight and food consumption in this group slightly increased while in group G4 no any significant changes were found. Therapeutic administration of Shankhpushpi as Churna as well as Kwatha significantly decreased PCM induced toxicity.